2004
DOI: 10.1210/en.2003-1435
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Augments Chondrocyte Hypertrophy and Reverses Glucocorticoid-Mediated Growth Retardation in Fetal Mice Metatarsal Cultures

Abstract: The study aims were to improve our understanding of the mechanisms of glucocorticoid-induced growth retardation at the growth plate and determine whether IGF-I could ameliorate the effects. Fetal mouse metatarsals were cultured for up to 10 d with dexamethasone (Dex; 10(-6) m) and/or IGF-I and GH (both at 100 ng/ml). Both continuous and alternate-day Dex treatment inhibited bone growth to a similar degree, whereas IGF-I alone or together with Dex caused an increase in bone growth. GH had no effects. These obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 45 publications
4
85
1
Order By: Relevance
“…Our previous studies have shown that IGF-I plays a major role in promoting longitudinal growth in the mouse metatarsal model (Mushtaq et al 2004). Furthermore, the growth inhibitory effect of dexamethasone was reversed in this model following exposure to IGF-I (Mushtaq et al 2004).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Our previous studies have shown that IGF-I plays a major role in promoting longitudinal growth in the mouse metatarsal model (Mushtaq et al 2004). Furthermore, the growth inhibitory effect of dexamethasone was reversed in this model following exposure to IGF-I (Mushtaq et al 2004).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the growth inhibitory effect of dexamethasone was reversed in this model following exposure to IGF-I (Mushtaq et al 2004). However, the growth inhibitory effects of TNF-a and IL-1b are only partially reversed following treatment with IGF-I (Martensson et al 2004), suggesting that some of the effects of these proinflammatory cytokines may be IGF-I independent.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…(43) The middle three metatarsals were isolated from 17-day-old embryos under a dissecting microscope. Metatarsals were cultured in 24-well plates (Costar, High Wycombe, UK) with one bone per well in 300 mL aMEM medium (without ribonucleosides) supplemented with 0.2% BSA (Fraction V), 5 mg/mL L-ascorbic acid phosphate, 1 mM b-glycerophosphate, 0.05 mg/mL gentamicin, and 1.25 mg/mL fungizone.…”
Section: Embryonic Metatarsal Organ Culturementioning
confidence: 99%
“…More recently, a number of investigators have used ex vivo models such as rodent metatarsals in culture (Mårtensson et al 2004, Mushtaq et al 2004. For example, when fetal mouse metatarsals were cultured for up to 10 days with either daily or alternate-day dexamethasone at 10 −6 M, dexamethasone-treated bones paralleled control bone growth rate until day 8 when their rate of growth decreased resulting in a total length that was significantly reduced from controls at days 8 and 10 (Mushtaq et al 2004).…”
Section: Techniques To Assess Bone Growth Ratementioning
confidence: 99%